Efek Pemberian Air Embun terhadap Gambaran Hematologi dan Biokimia Darah - Widowati, Lucie; Astuti, Yun; Winarno, M. Wien (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2012)
Circulation disorder of blood at a person is related to metabolic process, and it can not be as the normal equilibirum, and later can affect to appearance of disseases. Dew water, can be produced from destilation process (Systemized Dew Process), filtered process and disinfection with ozoniation. Dew water is stated can be used for disorder of blood circulation treatment. For the examination effect of dew water for blood circulation disorder, dew water was tested for blood description and biochemistry blood description at the animal model with cholesterol diet.It was the experimental pharmacology method, with the blood description as hamoglobline, erythrocyte, leucocyte, thrombocyte, hematochrite value; biochemistry description as total cholesterol, LDL cholesterol, HDL cholesterol, trigliserid; freeze time of blood; the arteri thickness ; body weight and the volume of intake water. Base on the normally of dosage at human, dew water intake for animal model were all day long admintration and of all of research time, every day for 2 month. The result of research has shown decrease of the body weight; increase need for intake water ; repairing haematology and biochemistry of blood, escpecially decrease of total cholesterol and LDL cholesterol; diluting blood; decreasing ateroschlerosis disorder at arteri vessel